The utilization of template matching method for license plate recognition: A case study in Malaysia - Norazira, A Jalil; Hasan Basari, Abd Samad; Salam, Sazilah; Ibrahim, Nuzulha Khilwani; Norasikin, Mohd Adili (2014)
Automatic License plate detection and recognition system is special form of optical character recognition and has been an active research domain in image processing field. However, the accuracy is varied due to different styles of number plates en-dorsed. Besides, the characters on Malaysia license plate are in one or two lines.Thus, the proposed license plate recognition (LPR) technique of this research is able to achieve the best recognition performance based on Malaysia license plate vehicle registration number characters. This paper presents a study of applying the template matching method for character image recognition. The database of characters and license plate image has been created by collecting images from various type of car. The initial pre-processing involves image enhancement, binarization, filtering and segmenting of license plate. There are 100 license plates that contain 693 characters have been tested, and the result shown that 92.78% of all characters is correctly recognized. Thus,template matching can be classified as one of the promising algorithm for recognizing Malaysia license plate.